Factors related to pregnancy status and unwanted pregnancy among lebanese women during the COVID-19 lockdown: a cross-sectional study - Chadia Haddad; Sandrella Bou Malhab; Hala Sacre; Diana Malaeb; Joelle Azzi; Dalia Khachman; Nathalie Lahoud; Pascale Salameh (BMC, 2022)
Abstract Background Home confinement and lockdowns have created challenges and vulnerabilities, causing relevant changes in sexual health and couple stability, particularly in women. The objective of this study was to evaluate the socio-economic and psychological factors related to current pregnancy status and unwanted pregnancy among Lebanese women during the COVID-19 lockdown. Methods A cross-sectional online study conducted between June 8 and August 1, 2020, enrolled 369 Lebanese women using the snowball technique for data collection. All married women between 18 and 51, with access to the internet and currently living with their partners, were eligible to participate. Current pregnancy status and unwanted pregnancy were assessed using binary questions. The SPSS software 25 was used for data analysis, and multivariable analysis was performed, taking the pregnancy status and unwanted pregnancy as the dependent variables. The statistical significance was set at a p-value < 0.05. Results Our results showed that 11.1% of women were pregnant, of whom 22.0% reported unwanted pregnancies. Having children (ORa = 0.183) and taking contraceptives (ORa = 0.231) were significantly associated with a reduced chance of becoming pregnant. Higher psychological violence would negatively affect pregnancy, but the association was not significant (p = 0.065). Regular visits to the physician for routine checks were also linked to a decreased risk of unwanted pregnancy (ORa = 0.053). Higher psychological violence would affect unwanted pregnancy; however, the association was insignificant (p = 0.056). Conclusion The study findings showed that having children and taking contraceptives are associated with a reduced pregnancy. Additionally, psychological violence was found to be related to current pregnancy status and unplanned pregnancy. During a pandemic, vulnerable women should be identified and given adequate care, knowledge, and awareness regarding their reproductive health.